Assessing the impact on inequalities in use of orthodontic services of the introduction of an objective measure of treatment need in Northern Ireland - Patel, Kishan; O'Neill, Ciaran (International Journal of Population Data Science, 2019)
Background with rationale Previous work has shown the existence of a sharp socio-economic gradient with respect to orthodontic services in Northern Ireland. The work demonstrated that those of lower socio-economic status had an odds ratio of 0.79 (95% CI 0.69 - 0.91) compared to those of higher socio-economic status with respect to the consumption of orthodontic services. In response to this, an objective measure of treatment need for such publicly funded services was introduced in 2014. Main Aim This study will use a record-linkage methodology to examine the relationship between use of publicly funded orthodontic care and the introduction of the index of treatment need (IOTN) in Northern Ireland in 2014. Methods/Approach Following a similar approach to that used previously, data related to use of orthodontic services was linked to socio-economic characteristics from the 2011 Census for members of the Northern Ireland Longitudinal Study. The relationship between socio-economic status and uptake of orthodontic services in the 3 years before and after the introduction of IOTN will be examined using an interrupted time series analysis as well as by the comparison of concentration indices across the study period. Results All results must be cleared by the Northern Ireland Statistical Research Agency before release. We expect cleared results to be available imminently and anticipate these showing a change in the uptake of publicly funded orthodontic services as well as a reduction in the socio-economic gradient over time. Conclusion The identification of inequalities in the use of publicly funded services requires an appropriate policy response. We anticipate that the introduction of IOTN as a criterion for access to publicly funded care will have successfully reduced the use of such services unrelated to need and the existence of inequalities in service use conditioned on need.